PEMBERDAYAAN EKONOMI KELUARGA MELALUI BUDIDAYA TIRAM DI GAMPONG TIBANG KECAMATAN SYIAH KUALA KOTA BANDA ACEH - Rasyidah, Rasyidah; Husna, Nurul; Safrianti, Liza (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This study examines the economic empowerment of families through the cultivation of oysters in Tibang Village. The potential of the people who work as fishermen have not fulfilled their basic family needs. Non-permanent fishing and the price that has fluctuated, has encouraged people to look for alternative businesses to increase income, including through the cultivation of oysters. This study aims to determine how the family oyster cultivation mechanism, as well as the economic condition of the family before and after conducting oyster cultivation in Tibang Village, Syiah Kuala District, Banda Aceh City. This study uses a descriptive method with a qualitative approach. The results of the study show that there are 40 families involved in the cultivation of oysters, this process makes it easy and practical to make the community always meet market demand because the supply of goods or oysters is sufficient. The process of cultivating oysters in Tibang Village through five stages, namely: land preparation, breeding, maintenance, harvesting and the final stage, namely cultivation. Oyster cultivation has also succeeded in increasing the economy of the community between housework. The average income of each family is Rp. 50,000 to Rp. 100,000 per day and this is done consistently because it does not depend on the season. Keywords: Family Eeconomic Empowerment, Oyster Cultivation